PENGGUNAAN MEDIA KANTONG BILANGAN DALAM MENINGKATKAN KETERAMPILAN MATERI PENGURANGAN - Yuyun Sri Wahyuni; Astri Sutisnawati; Luthfi Hamdani Maula (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
three components is crucial. Besides these three components, learning methods or strategies, learning tools are also absolutely necessary. The formulation of the problem in this research is how to use Number Pockets media in improving the material reduction skills of class I SD Negeri Linggamanik in Mathematics. This research aims to improve students' ability to operationalize subtraction with the help of Number Pockets, it is also hoped that it will be useful for students, researchers, and parents of students to achieve this goal. Conducted class action research for class I SD Negeri Linggamanik as many as 20 students, which was carried out in two cycles. The media used in this study is a qualitative approach that describes the real problems that exist in the field and is then reflected and analyzed based on supporting theory followed by the implementation of research in the field. The data obtained in this study through observation, discussion and evaluation. The results of this study showed an increase in the Pre-cycle, Cycle I and Cycle II activities. In the Pre-cycle study, 15% of students experienced mastery learning after the action was carried out using the Number Bag tool. The mastery of student learning in cycle I rose to 45% followed by the next cycle of all students experiencing mastery of learning. The conclusion that can be drawn is that number bag media can assist students in operationalizing number subtraction in grade I mathematics learning. So that learning achievement is progressing. Another finding is that children become happy, confident in carrying out the learning process. Thus it can be suggested that the implementation of education should be environmentally sound because the environment provides many tools.